Chapter 4 — Restoring Trees After a Hurricane - Edward F. Gilman; Traci Partin (EDIS)
ENH-1054, a 10-page full-color fact sheet by Edward F. Gilman and Traci Partin, is part of the Urban Forest Hurricane Recovery Program series. It provides a step-by-step guide for restoring trees after a hurricane or windstorm so that trees can bring beauty and shade back to the community with reduced risk. Published by the UF Department of Environmental Horticulture, September 2007.